Clareza e distinção das ideias: uma abordagem peirciana - Fanti, Renato (2013)
This work aims to address some aspects of the concept of clearness in the work of Charles Sanders Peirce (1839-1914), as opposed to the one consolidated view in the History of Philosophy, known as Rationalism, undertaken by René Descartes (1596-1650). It presents a brief exposition of what the latter meant by this concept. Next we will approach the historical context in which Peirce was inserted, highlighting the characters for the current scientific paradigm, the one presented by him at the meetings at the Metaphysical Club in Cambridge (1872), as an analysis of his Phenomenology, considered fundamental to situ-ate the concept that he intended to elaborate. Turning then to the Cartesian Critical Spirit, thus branded by Peirce, we will refer to Descartes substantial contributions which brought about a new scientific and philosophical vision, thus disrupting with the prevailing Scholastic attitude, and to the concept of Carte-sian intuition, when we will be ready to tackle Peirce s essay How To Make Our Ideas Clear (1878), which contains his Pragmatist Maxim, and which advances the author s concept of clarity. Finally, we will also supply an example of such scientific clarity as exposed in his essay, Three Types of Reasoning (1903)